2014
DOI: 10.2478/s13380-014-0225-7
|View full text |Cite
|
Sign up to set email alerts
|

Neuroinflammation and Alzheimer’s disease: lessons learned from 5-lipoxygenase

Abstract: Aside from the well-known amyloid beta and tau pathologies found in Alzheimer's disease (AD), neuroinflammation is a well-established aspect described in humans and animal models of the disease. Inflammatory perturbations are evident not only in neurons, but also in non-neuronal cells and cytokines in the AD brain. Although the amyloid hypothesis implicates amyloid beta (Aβ) as the prime initiator of the AD, brain inflammation in AD has a complex relationship between Aβ and tau. Using our work with the 5-lipox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…In contrast to the amyloid cascade hypothesis of AD, which implies that tau pathology is a secondary, downstream phenomenon, the neuropathological findings of Braak and collaborators have fueled a significant controversy concerning the importance or contributions of Aβ burden in producing damage compared to that caused by tau pathology. Additionally, in AD, the pathological Aβ and tau proteins mutually interact and are influenced by many other contributors, such as inflammatory [ 125 ], vascular, and environmental factors, as well as compensatory neuroplastic responses to counteract neural injury associated with neurodegenerative processes [ 126 ], all of which may promote cognitive and behavioral decline.…”
Section: Selective Overview Of Major Discoveries On Tau Protein Anmentioning
confidence: 99%
“…In contrast to the amyloid cascade hypothesis of AD, which implies that tau pathology is a secondary, downstream phenomenon, the neuropathological findings of Braak and collaborators have fueled a significant controversy concerning the importance or contributions of Aβ burden in producing damage compared to that caused by tau pathology. Additionally, in AD, the pathological Aβ and tau proteins mutually interact and are influenced by many other contributors, such as inflammatory [ 125 ], vascular, and environmental factors, as well as compensatory neuroplastic responses to counteract neural injury associated with neurodegenerative processes [ 126 ], all of which may promote cognitive and behavioral decline.…”
Section: Selective Overview Of Major Discoveries On Tau Protein Anmentioning
confidence: 99%
“…In contrast to the amyloid cascade hypothesis of AD, which implies that tau pathology is a secondary, downstream phenomenon, the neuropathological findings of Braak and collaborators have fueled a significant controversy concerning the importance or contributions of Aβ burden-induced damage compared to that caused by tau pathology, particularly in LOAD. Additionally, the pathological Aβ and tau proteins mutually interact and are influenced by many other factors, such as epigenetic (Lardenoije et al, 2015), inflammatory (Joshi and Praticò, 2014), vascular, and possibly direct environmental causes (metals, metalloids, pollutants, various compounds in food), as well as compensatory neuroplastic response to counteract neural injury associated with neurodegenerative processes (Wang et al, 2011), all of which may promote cognitive and behavioral decline.…”
Section: Clinical and Neuropathological Criteria For Ad Diagnosismentioning
confidence: 99%
“…Aside from Aβ, tau and synaptic pathology, activation of microglia and astrocytes is another important feature found consistently in the AD brain, and some work even suggests that these cells play a functional role in AD pathogenesis. 30 Interestingly, in our study we observed that expression levels of CD45 and GFAP, molecular markers of microglia and astyrocytes activation, respectively, were significantly reduced in the group of mice receiving the active drug.…”
Section: Discussionmentioning
confidence: 45%